Measuring Innovation in Managerial Disclosures Predictive Insights and Managerial Incentives - Ardi Armen (LPPM STIE Kasih Bangsa, 2024)
This research investigates the role of innovation in managerial disclosures, focusing on predictive insights and managerial incentives. By analyzing a comprehensive range of studies, the review identifies key themes and trends that underscore the importance of innovative disclosure practices. The findings highlight that forward-looking statements and non-financial metrics significantly enhance investor confidence and firm valuation. Additionally, the alignment of managerial incentives with long-term performance metrics is crucial for promoting transparency and innovation. Effective corporate governance mechanisms are essential for designing incentive structures that encourage managers to engage in innovative activities and provide comprehensive disclosures. The insights gained from this review provide a foundation for future research and practical implications for firms seeking to enhance their disclosure practices and align managerial incentives with long-term goals.